2014
DOI: 10.1186/s12913-014-0588-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety risks associated with telecare: a systematic review and narrative synthesis of the literature

Abstract: Background: Patient safety risk in the homecare context and patient safety risk related to telecare are both emerging research areas. Patient safety issues associated with the use of telecare in homecare services are therefore not clearly understood. It is unclear what the patient safety risks are, how patient safety issues have been investigated, and what research is still needed to provide a comprehensive picture of risks, challenges and potential harm to patients due to the implementation and use of telecar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 77 publications
(167 reference statements)
1
68
0
5
Order By: Relevance
“…However, a previous review of health technologies and their impact on the quality and safety of healthcare delivery identified a large gap between the postulated and empirically demonstrated benefits (Black et al, 2011). Furthermore, another review performed to identify patient safety risks associated with telecare use in homecare identified a need for more research to avoid or minimize potential harm to patients (Guise, Anderson, & Wiig, 2014). Qualitative research concerning safety in telecare use has addressed specific telecare interventions such as safety alarms (Melander-Wikman, Fältholmand, & Gard, 2008;Melkas, 2010), fall detectors and bed occupancy sensors (Horton, 2008) and smoke detectors (Doughty & Orton, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous review of health technologies and their impact on the quality and safety of healthcare delivery identified a large gap between the postulated and empirically demonstrated benefits (Black et al, 2011). Furthermore, another review performed to identify patient safety risks associated with telecare use in homecare identified a need for more research to avoid or minimize potential harm to patients (Guise, Anderson, & Wiig, 2014). Qualitative research concerning safety in telecare use has addressed specific telecare interventions such as safety alarms (Melander-Wikman, Fältholmand, & Gard, 2008;Melkas, 2010), fall detectors and bed occupancy sensors (Horton, 2008) and smoke detectors (Doughty & Orton, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the first issue, it has indeed been found that technical problems and poor device quality can adversely affect the quality and safety of telecare services. [30] As this is doubtless a very real concern for healthcare professionals faced with the implementation and use of telecare services, [8] it needs to be taken seriously by home healthcare managers, telecare implementation managers, and technology providers alike. In regard to the second concern, the participants themselves were quick to note that the potential for medication errors, where patients miss a dose, take it at the wrong time, take an incorrect dose, or the incorrect medication, is not exclusive to the telecare context but rather a very common patient safety issue within the home healthcare setting in general.…”
Section: Discussionmentioning
confidence: 99%
“…[29] There have however been very few reports of simulation-based telecare training initiatives aimed at qualified healthcare professionals. [30] We have found one such study, by Rutledge and colleagues, [12] which notes positive outcomes in using standardized patient simulations to introduce registered nurses to remote nursing care via audiovisual technology. In addition, a handful of studies have found simulation to be a useful approach to telecare training aimed at pre-registration nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…40 In the UK, barriers to adoption have included fears that technology may compromise patient confidentiality and undermine patient safety. [41][42][43] There are also cultural and behavioural barriers, 44 including concerns about the possible erosion of clinicians' autonomy.…”
Section: Technologymentioning
confidence: 99%